EXPLORING STUDENTSâ€™ RESPONSE TO PEER FEEDBACK STRATEGY IN EFL WRITING CLASS - Anni Rachmayani; Ahmad Rifai; Tedi Rohadi (IAIN Syekh Nurjati Cirebon, 2018)
Alwasilah, A. Chedar, &Alwasilah, Senny, S. 2013. PokoknyaMenulis. Bandung: PT KiblatBukuUtama.BerÄÃkovÃ¡, Pavlina. 2007. Teacherâ€™s Role in Pair Work. A Thesis: Faculty of EducationDepartment of English Language and Literature. Brno:Masaryk University.Bijami, M., Kashef, S.H., &Nejad, Maryam, S. 2013. 'Peer Feedback in Learning English Writing: Advantages and Disadvantages. Journal of Studies in Education, 2013, Vol. 3, No. 4. 91-97. Malaysia: Macrothink Institute.Biri H. 2014. Contribution of Peer Assessment Method to Teacher Education. Unpublished Master's Thesis. Karadeniz Technical University Institute of Educational Sciences, Trabzon.Brown, H. Douglas. 2002. Teaching by Principles: An Interactive to Language Pedagogy (2nd ed.). London: Longman.Byrne, Donn. 1989. Techniques for Classroom Communication. UK: Longman.Creswell, John, W. 2013. Educational Research: Planning, Conducting and Evaluating Quantitative and Qualitative Research. Fourth Edition. Boston: Pearson Education Inc.Griffiths, B. Teacher Positioning in the Classroom. 2005. Teaching English. British Council.Hadfield, J. 1992. Classroom Dynamics. Oxford University Press.Hyland, Ken, & Hyland, Fiona. 2006. Language Teaching: Feedback on Second Language Students' Writing. United Kingdom: Cambridge University Press. Language Teaching 2006, Volume 39, No.2. P. 83-1901 (Available on http://hdl.handle.net/10722/57356)Keppell M, and Carless D. 2006. Learning-Oriented Assessment: A Technology-Based Case Study. Assessment Education, 13 (2): 179-191.Kurihara, Noriko. 2017. 'Peer Review in an EFL Classroom: Impact on the Improvement of Student Writing Abilities'.The Asian Journal of Applied Linguistics. Vol. 4 No. 1, 2017, 58-72.Musa, F., Mansor, A. Z., Mufti, N., Aida, N. A., & Dato's Kasim, F. 2012. Negotiation Skills: Teachers' Feedback as Input Strategy. Procedia- social and Behavioural Sciences, 59, 221-226.Nelson, G. & Carson, J. 1995. Social Dimensions of Second-Language Writing Instruction: Peer Response Groups as Cultural Context. In D. Rubin (Ed.), Composing social identity in Written Communication (pp. 89-109). Hillsdale, NJ: Lawrence Erlbaum.Nicole, D., & Macfarlane-Dick, D. 2006. Formative Assessment and Self-Regulated Learning: A Model and Seven Principles of Good Feedback Practice. Studies in Higher Education, 31(2), 199-218.Noor, Mochammad. 2016. â€˜Improving the Ability in Writing Narrative Text of Junior High School Students through Peer Feedbackâ€™. Indonesian Journal of English Language Teaching and Applied Linguistics. Vol 1, No 1, 11-21.Orsmond, P., Maw, S. J., Park. R. J., Gomez, S., & Crook, C. A. 2013. Moving Feedback Forward: Theory to Practice. Assessment & Evaluation in Higher Education, 38(2), 240-252.Ã–zdemir, Serpil. 2016. The Opinions of Prospective Teachers on Peer Assessment. Educational Research and Reviews. Vol. 11 (20), pp. 1859-1870, 2016.Saito, H., & Fujita, T. 2004. Language Teaching Research.Characteristics and User Acceptance of Peer Rating in EFL Classrooms.Vol 8 (1), pp. 31â€“54.Seow, Anthony. 2002.The Writing Process and Process Writing. Richard, Jack, C. &Renandya, A. Willy.In Methodology in Language Teaching: An Anthology of Current Practice. Cambridge: Cambridge University Press.Siregar, M. Ibrahim, &Murni, Sri, Minda. 2013. 'The Application of Peer Feedback Strategy to Improve Student's Writing Achievement in Narrative Text'. LINGUISTICA Journal of Linguistics of FBS UNIMED. Vol. 2, No. 1, 2013.Vygotsky, L. 1978. Mind in Society: The Development of Higher Psychological Processes. Cambridge, MA: Harvard UniversityPress.Watcyn-Jones, Peter & Howard-Williams, Deirdre. 2002. Pair Work 1 (Elementary-Pre-Intermediate). UK: Penguin English Books.Zariski, A. 1996. Students Peer Assessment in Tertiary Education: Promise, Perils and Practice. In Teaching and Learning Within and Across Disciplines: Proceedings of the 5th Annual Teaching Learning Forum, ed. J. Abbott and L. Willcoxson. Perth: Murdoch University.